2017
DOI: 10.1589/jpts.29.1201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lingual strength training on lingual strength and articulator function in stroke patients with dysarthria

Abstract: [Purpose] This study investigated the effects of lingual strength training (LST) on lingual strength and articulator function in stroke patients with dysarthria. [Subjects and Methods] 16 stroke patients with dysarthria were randomly assigned into two groups: the experimental group (n=8) or the control group (n=8). Both groups received the conventional rehabilitation therapy at 30 min/day, 5 times for week, and during 4 weeks, and the experimental group received an additional 30 min of LST using the Iowa Oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Table 1 summarizes the available literature on the efficacy of TSE, with the majority of studies reporting significant increases in TS following TSE. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] However, only half of the available research was executed in pathological groups. 19,22,24,25,[27][28][29][30][31] Concerning swallowing, half of the reported studies reported effects of TSE on swallowing function.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the available literature on the efficacy of TSE, with the majority of studies reporting significant increases in TS following TSE. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] However, only half of the available research was executed in pathological groups. 19,22,24,25,[27][28][29][30][31] Concerning swallowing, half of the reported studies reported effects of TSE on swallowing function.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] However, only half of the available research was executed in pathological groups. 19,22,24,25,[27][28][29][30][31] Concerning swallowing, half of the reported studies reported effects of TSE on swallowing function. 19,21,22,24,25,[27][28][29]31 Results were inconclusive, with three studies reporting an increased swallowing efficiency, for example, a decrease of oropharyngeal residue, in stroke patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,53 In addition, execution variability, whether in assessment and training programs, may interfere with study results, and a fixed protocol of sessions provides a better understanding of the effect of the programs, 56 as observed in four of the five studies involving the IOPI therapy. 43,44,47,57 Despite the variability in the proposed tongue strength training programs, 43,44,46 it was observed that most participants in the reviewed studies received training programs ranging from 6 to 8 weeks and the sessions were held at 3 to 5 days a week, which meets recent literature recommendations for tongue training program. 57 Protocols for training using the IOPI 43,44,47,57 reflect much of what the first studies proposed by Robbins in 2005, and because of their reliability most of them remain almost unchanged.…”
Section: Discussionmentioning
confidence: 63%
“…We are not aware of previous studies exploring the impact of TSE exercise frequency in outcomes. Reported training frequencies for TSE vary from 1 to 7 times per week [6,7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] with the majority exercising at 3 [6,7,18,20,21,30] or 5 times per week [17,[25][26][27]29]. Detraining effects have been reported at 4 [24] and 8 weeks [30] after treatment, both in young healthy adults.…”
Section: Introductionmentioning
confidence: 99%